Nucleated red blood cells as a prognostic indicator in dogs with anemia - Hollmann, F.; Geisen, V.; Hartmann, K.; Doerfelt, R. (Frontiers in Veterinary Science, 2025)
BackgroundIn human medicine, nucleated red blood cells (NRBCs) in the peripheral blood have been associated with a poor prognosis and increased mortality in critically ill patients. In critically ill dogs, mortality was also significantly associated with high peripheral NRBC count.ObjectiveThis study aimed to determine the presence of NRBCs in the peripheral blood of dogs with regenerative and non-regenerative anemia and to evaluate the prognostic relevance of NRBCs in anemic dogs. Furthermore, the correlation between NRBCs and other blood parameters was examined.Materials and methodsMedical records of 254 anemic dogs hospitalized from November 2013 to June 2020 were retrospectively reviewed. Inclusion criteria were a hematocrit of <30%, a minimum age of 6 months, and the presence of a manual blood smear evaluation. Data were analyzed using Fisher’s exact test, Mann–Whitney U test, Kruskal-Wallis test with Dunn’s post-hoc multiple comparison test, and Spearman correlation. p-values <0.05 were considered significant.ResultsOne hundred ninety-one of 254 patients had NRBCs in their blood smear. The absolute NRBC count was significantly higher in dogs with regenerative anemia [1,514/μl (92–40,810/μl)] compared to dogs with non-regenerative anemia [220/μl (10–5,260/μl); p < 0.001]. NRBCs were more often present in dogs with regenerative anemia (141/167) than in dogs with non-regenerative anemia (35/62; p < 0.001). The NRBC concentration was not different between surviving and non-surviving dogs (p = 0.080). An increase or decrease of NRBCs during hospitalization was also not associated with outcome.ConclusionNRBCs commonly appear in the peripheral blood of dogs with regenerative anemia. Their presence and quantity are not associated with survival.